Takhrīj "extraction " of the Branches from Exceptional Uṣūl " principles of jurisprudence" According to Abu al- Khattab - Al- Faris, Sarah Ibrahim (Journal of Islamic Sciences, 2021)
This research aims at showing the fruit of the fundamentals of jurisprudence science. Principles of Jurisprudence science gains status through linking it to its fruit which is training on deriving jurisprudential rulings and choosing the best ruling, branching out issues and building them on evidence, as well as gaining knowledge of the imams’ opinions on topics about which there is no text and on the rulings of emergent calamities as well. If it were only a theoretical science with no application, then it would be useless; a scourge for its owner. The fundamentals of jurisprudence science must be linked to its fruit for its benefit to be complete. The science of Takhrīj ‘extraction’ and branching has a close relationship with the science of usul al- fiqh, as it brings it out from the theoretical to the practical, pragmatic side. Thus, it is of great benefit and great importance for the one studying this field of science. The research also explains the approach of imam Abu al- Khattab; an important Hanbali imam by highlighting his rules and linking them with jurisprudential branches, and identifying the extent of the contravention and approval, especially in the section on Exceptional Uṣūl "principles" depending on the inductive analytical approach.